Unlocking the Genetic Diversity and Population Structure of a Wild Gene Source of Wheat, Aegilops biuncialis Vis., and Its Relationship With the Heading Time - Ivanizs, László; Monostori, István; Farkas, András; Megyeri, Mária; Mikó, Péter; Türkösi, Edina; Gaál, Eszter; Lenykó-Thegze, Andrea; Szőke-Pázsi, Kitti; Szakács, Éva; Darkó, Éva; Kiss, Tibor; et al. (Frontiers in Plant Science, 2019)
Understanding the genetic diversity of Aegilops biuncialis, a valuable source of agronomical useful genes, may significantly facilitate the introgression breeding of wheat. The genetic diversity and population structure of 86 Ae. biuncialis genotypes were investigated by 32700 DArT markers with the simultaneous application of three statistical methods - Neigbour Joining clustering, Principal Coordinate Analysis and the Bayesian approach to classification. The collection of Ae. biuncialis accessions was divided into five groups that correlated well with their eco-geographic habitat: A (North Africa), B (mainly from Balkans), C (Kosovo and Near East), D (Turkey, Crimea and Peloponnese) and E (Azerbaijan and the Levant region). The diversity between the Ae. biuncialis accessions for a phenological trait (heading time), which is of decisive importance in the adaptation of plants to different eco-geographical environments, was studied over three years. A comparison of the intraspecific variation in the heading time trait by means of ANOVA and Principal Component Analysis revealed four phenotypic categories showing association with the genetic structure and geographic distribution, except for minor differences. The detailed exploration of genetic and phenologic divergence provides an insight into the adaptation capacity of Ae. biuncialis, identifying promising genotypes that could be utilized for wheat improvement.